Connectedness of Dynamic Volatility Over Green Cryptos, the ESG Indices, and Gold: TVP-VAR Approach - Nevi Danila (SAGE Open)
This study investigates the dynamic volatility transmission among green cryptocurrencies, ESG indices, and gold from 2018 to 2023, offering insights valuable to portfolio managers for risk management. We selected four green cryptocurrencies, three ESG indices, and gold as examples. We utilize the time-varying parameter vector autoregression (TVP-VAR) model to examine the relationships among the assets. This approach aims to analyze the dynamic interactions among many time series variables whose relationships fluctuate over time. Key findings include volatility patterns; that is, Gold, Tezos, Nano, and DJSEM exhibit higher volatility, while Cardano, Stellar, DJSW, and DJSNA show lower volatility. Gold plays a net volatility role, meaning it is a net receiver of volatility. Among green cryptocurrencies, Cardano and Stellar are net transmitters, while Nano and Tezos are net receivers. For ESG indices, DJSW and DJSNA are net transmitters, whereas DJSEM is a net receiver. While diversification across different asset classes is beneficial, the most effective hedging occurs within the same asset class, such as cryptocurrencies. The mixed outcomes prevent a clear categorization of asset classes as net transmitters or receivers, highlighting the complexity of volatility interactions. Policymakers should account for the systemic risk linked to green cryptocurrencies and ESG indices when formulating legislation.